KINERJA DOSEN DALAM MENINGKATKAN KEMAMPUAN AKADEMIK (HARD SKILL) DAN PENGUASAAN KETERAMPILAN (SOFT SKILL) PADA MAHASISWA PKK FKIP UNSYIAH - Zahraini Zahraini (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
The performance of the lecturers is important factor in order to ensure the quality management of a college. The lecturers performance at PKK study program FKIP Unsyiahis truly play role in producing students not only work in government with satisfying academic grade (hard skill) but also students must be able to create their own work field by possessing skill (soft skills) to take over the world work. This study aims at knowing the ability, motivation, disciplines, responsibility, and supporting factors on the lecturers performance in improving academic competence and skill acquisition of the students at PKK, FKIP Unsyiah. This study used a qualitative approach through data collecting techniques i.e. documentation, observations , and interviews. The subjects of the research were the dean, deputy dean of academic affairs, the chairman of the PKK department, lecturers, laboratory chairman, and students. This study shows that 1) The ability of the lecturers in carrying out teaching can be seen through arrangement of the lecturing material, lecturing implementation, and evaluation. 2 ) Motivation in conducting lectures , that the PKK lecturers of FKIP Unsyiah have conducted real efforts to reach the decided aim, but few lecturers less motivated the students optimally, lack of guiding of the lecturers or their seniors as well as program chairman, action less than optimal motivation lecturer , received guidance from lecturers more senior or chief Prodi . 3) The lecturers discipline is reflected through factual time in implementing the lecture, obeying the obtain rules and conducting continuously. Lecturer’s discipline reflected by timeliness in implementing the course, follow the rules, and do it continuously. 4) The lecturer’s responsibility and commitment in implementing the lecturer can be seen through guiding the students in accordance with the main duty and its function. 5) Improving performance in academic competence and skill acquisition are supported by several factors such as faculty development program by sending lecturers to follow the profession asosiation programs, workshops, seminars , and training on professional development.